Tumor budding as a predictor for prognosis and therapeutic response in gastric cancer: A mini review - Xue, Chi; Du, Yuwei; Li, Yuegang; Xu, Huimian; Zhu, Zhi (Frontiers in Oncology, 2023)
In recent years, the role of tumor budding in gastric cancer has received increased attention across a number of disciplines. Several studies have found associations between tumor budding and the prediction of lymph node metastasis in early gastric cancer, prognosis of advanced gastric cancer, predictors of therapeutic response to immune checkpoint inhibitors, such as microsatellite instability (MSI), and therapeutic targets of molecular targeted therapy, such as human epidermal growth factor receptor 2 (HER-2). Therefore, tumor budding is a major element in the formulation of risk stratification and precision medicine strategies for patients with gastric cancer.